Synthesis of four arms star polymer for hydrogel formulation - Ismail, Mohamad Wafiuddin; Abdul Khodir, Wan Khartini; Daik, Rusli; Abd Hamid, Shafida; Darnis, Deny Susanti (2018)
Star-shaped polymer can be described as macromolecules with multi-armed polymeric material with a huge potential in biomedical applications. This study investigated the effect of molecular architecture of amphiphilic star polymers in drug formulation for wound healing application. Four arms star-shaped block copolymers constructed of polyethylene glycol (PEG) as hydrophilic block and polycaprolactone (PCL) as hydrophobic block were synthesized via combination of Steglich Reaction and ring opening polymerization (ROP). 1H NMR and FTIR analysis shows that the four star-shaped polymers is successfully synthesized. XRD analysis of the polymers shows that PEG decrease the crystallinity of the polymers. Thermal analysis (XRD and DSC) shows the thermal stability difference between homopolymer star and block copolymer star in which modification of end-group affect their thermal stability. The polydispersity index (PDI) indices from GPC were narrow suggesting controlled polymerization reaction. Preparation of hydrogel formulation shows the presence of PEG in the polymers increase the hydrophilicity and solubility in water. Drug loading of the formulation with Ciprofloxacin as drug cargo indicating high entrapment efficiency of the drug towards star-shaped polymer formulation.